2023
DOI: 10.1021/acssuschemeng.3c00636
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic and Life Cycle Analyses of Thermochemical Upcycling Technologies of Low-Density Polyethylene Waste

Abstract: In this study we compare techno-economics and life cycle assessment of thermochemical depolymerization technologies, including pyrolysis, gasification, hydrocracking, hydrothermal liquefaction, and hydrogenolysis, to generate various products from low-density polyethylene (LDPE) waste. We elucidate the effects of production scale, collection cost, and concentration of LDPE in plastic waste. Pyrolysis of LDPE to olefins followed by their conversion to lubricant oils is the most profitable technology. Hydrogenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Next, the annual costs of different selective collection schemes from urban areas (weekly, fortnightly, or monthly collection frequencies) are estimated using OptiFlow Route Optimization software . The annual costs of mechanical recycling of nonhousehold end-use plastic film are estimated by combined material flow analysis (MFA) in the recycling plant and economic assessment, as suggested by Larrain et al, Hernández et al, and Bashirgonbadi et al The required inputs for the MFA model are waste quantity and composition, recycling plant configuration, and separation efficiency of equipment used in the recycling plant. Later, the MFA results and data on capital investment and utility consumption are used as the basis for the economic assessment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, the annual costs of different selective collection schemes from urban areas (weekly, fortnightly, or monthly collection frequencies) are estimated using OptiFlow Route Optimization software . The annual costs of mechanical recycling of nonhousehold end-use plastic film are estimated by combined material flow analysis (MFA) in the recycling plant and economic assessment, as suggested by Larrain et al, Hernández et al, and Bashirgonbadi et al The required inputs for the MFA model are waste quantity and composition, recycling plant configuration, and separation efficiency of equipment used in the recycling plant. Later, the MFA results and data on capital investment and utility consumption are used as the basis for the economic assessment.…”
Section: Methodsmentioning
confidence: 99%
“…The economic assessment of nonhousehold end-use plastic film waste management demonstrates the difference between the costs incurred by waste collection (i.e., the results of the logistic simulation) and mechanical process and the revenue from regranulate sales, i.e., rPE basic/advanced . ,,, The estimation of capital investment for the mechanical recycling plant follows the approach described by Sinnott and Towler, which is also applied in previous studies. The estimated total investment includes the price of individual recycling equipment (in Figure ) and additional procuring, transport, installation, and running test of the equipment, engineering and project management, and site infrastructure (i.e., building the recycling plant itself). The total investment per piece of equipment is provided in Table SI5, and the economic modeling parameters are provided in Table SI6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass and energy balance from the BioSTEAM process models were used for capital and operating cost estimates. The study employs the discounted cash flow rate of return (DCFROR) commonly used in similar studies ,, to estimate the net present value (NPV) of each scenario. The NPV was selected as the economic indicator to compare the scenarios because it allows for straightforward economic feasibility estimates and multiple technology comparison for multi-product facilities.…”
Section: Techno-economic Analysismentioning
confidence: 99%
“…To the best of our knowledge, no study has investigated the economic feasibility and life cycle assessment of thermal oxo-degradation or compared the technology to conventional pyrolysis of waste plastics. Some studies have compared the economics and environmental impacts of various chemical recycling technologies for converting waste plastics into value-added products. , Hernández et al have compared the techno-economic analysis (TEA) and life cycle assessment (LCA) of pyrolysis, hydrogenolysis, gasification, hydrocracking, and hydrothermal liquefaction of low-density polyethylene waste (LDPE) to produce different products. The study found the pyrolysis of LDPE to olefins, followed by the conversion to lubricant oil, to be the most profitable thermochemical upcycling technology for LDPE, with a return on investment (ROI) between 13 and 17% .…”
Section: Introductionmentioning
confidence: 99%